HUBUNGAN BUDAYA ORGANISASI DAN MOTIVASI TERHADAPORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN EFEKTIVITASORGANISASI PADA KANTOR REGIONAL XI MANADO DAN XIIPEKANBARU BADAN KEPEGAWAIAN NEGARA - Rahayu, Sri (Jurnal Tepak Manajemen Bisnis, 2016)
The Purpose of this study was to determine whether organizational culture andmotivation toward Organizational Citizenship Behavior (OCB) and OrganizationEffectiveness of Badan Kepegawaian Negara Regional Office XI Manado and XIIPekanbaru. The population of this study is 141 employees with a number ofresearch samples are 104 employees.This study used questionnaire for collectingthe data, data analysis method which is used is trimming of the path analysismodel, processing the data used SPSS 19.0 to test the reliability, validity, partial(T test) and simultaneous test (F test)The model used in this study consists ofthree sub-structure of the first structure are Organizational Culture, andMotivation. The second structure are Organizational Culture, Motivation andOCB, while the third structure consist of Organizational Culture, Motivation,OCB and Organization Effectiveness, in this structure motivation variable mustremove from model because does not have a significant impact on theeffectiveness of the organization.Based on the findings of research can beconcluded thatthe organizational culture have a direct influence on motivation.Organizational culture along with motivation have direct effect on OCB.Organizational Culture direct and significant impact on the effectiveness of theOrganization as well as indirectly through the OCB. Motivation while no directimpact on Organizational Effectiveness.